2022
DOI: 10.1038/s41586-022-04723-z
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of sodium-dependent bile salt uptake into the liver

Abstract: The liver takes up bile salts from blood to generate bile, enabling absorption of lipophilic nutrients and excretion of metabolites and drugs1. Human Na+–taurocholate co-transporting polypeptide (NTCP) is the main bile salt uptake system in liver. NTCP is also the cellular entry receptor of human hepatitis B and D viruses2,3 (HBV/HDV), and has emerged as an important target for antiviral drugs4. However, the molecular mechanisms underlying NTCP transport and viral receptor functions remain incompletely underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 73 publications
(91 reference statements)
2
50
0
2
Order By: Relevance
“…The cryo-EM structure of human NTCP (PDB: 7PQQ) [14] was visualized with Protean 3D DNASTAR Software. Visual representation of fluctuation in protein structure and interatomic interactions at amino acid position 146 of wt and mutant NTCP proteins was performed using DynaMut2 server based on the AlphaFold model of human NTCP (AF-Q14973-F1) [26,28].…”
Section: Modelling Of Human Ntcpmentioning
confidence: 99%
See 4 more Smart Citations
“…The cryo-EM structure of human NTCP (PDB: 7PQQ) [14] was visualized with Protean 3D DNASTAR Software. Visual representation of fluctuation in protein structure and interatomic interactions at amino acid position 146 of wt and mutant NTCP proteins was performed using DynaMut2 server based on the AlphaFold model of human NTCP (AF-Q14973-F1) [26,28].…”
Section: Modelling Of Human Ntcpmentioning
confidence: 99%
“…Interestingly, G158R mutation of human NTCP completely abolished susceptibility to HBV and HDV infection, while the R158G exchange was sufficient to transmute the old world monkey Ntcp to a functional HBV/HDV receptor [11]. Based on recently published cryo-electron microscopy (EM) structures [13][14][15], NTCP can undergo a conformational transition from an outward-to an inward-facing state, whereby opening of a relatively wide transmembrane pore/tunnel allows substrate translocation from the extracellular to the intracellular compartment. In addition, cryo-EM analysis of preS1-bound NTCP suggested that the myr-preS1 peptide binds preferentially to the open-pore state of the carrier and thereby competes with bile acids for binding to residues lining the same cavity [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations